Implementation of System Dynamics to Increase Successful Utilization of E-Commerce with Marketing and Innovation Capability in MSMEs - Anindo Saka Fitri; Seftin Fitri Ana Wati; Eristya Maya Safitri; Anita Wulansari; Dhian Satria Yudha Kartika (Internasional Journal of Data Science, Engineering, and Anaylitics, 2022)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economic development of many cities around the world. The role of MSMEs can encourage equitable economic development which is one of the main pillars of the ASEAN Economic Community (AEC). But unfortunately, there are still many people who do not know how to market a new product and have a large market potential by using internet technology. The ongoing COVID-19 pandemic is causing changes in individual habits which also has the opportunity to permanently influence market developments in the coming years. Many people choose to shop online using e-commerce. The role of e-commerce is very influential in improving the performance of MSMEs. There are several variables in the successful use of e-commerce, including internal and external inhibiting and supporting variables. This study applies the system dynamics method to link the variables of success in the use of e-commerce with variables related to the performance of MSMEs. The results of this study are the success of the use of e-commerce is interrelated with marketing and innovation capability which has a positive effect on the performance of MSMEs. This research is expected to increase the success of using e-commerce in MSMEs, especially in Indonesia.